Marx´s Coat Workshop: : Between Fashion, Design, Anthropology and Semiotics (Revista de Ensino em Artes, Moda e Design, 2020)
The paper aims to analyze the workshop “The coat of Marx,” designed and coordinatedby Maira Gouveia. The workshop is an action inspired by the coat’s poetics overlays with itsusers reported in Peter Stallybrass’s same title’s book (2012). As a methodology, the workshophas a practical-reflective character. It proposes exercises that dialogue with the fields of semioticsand anthropology, using questions and reflections from fashion theory and the field ofdesign to weave a critical-reflective reading on the possibilities of relationships to be built witheveryday objects. Throughout the investigation, it was possible to observe ways of occurringdialogues between design, fashion, anthropology, and semiotics to rethink our look at materialculture. Moreover, the workshop proposes a more significant relationship with the artifactssurrounding us, from Karen Barad’s agential realism to think in the workshop, the possibility ofunderstanding objects as social agents as co-creators of our ways of living.